1996
DOI: 10.1177/030098589603300211
|View full text |Cite
|
Sign up to set email alerts
|

p53 Tumor Suppressor Protein Overexpression in Osteogenic Tumors of Dogs

Abstract: Abstract. Alterations in the p53 tumor suppressor gene have been implicated in the genesis and/or progression of the majority of human cancers, including osteosarcoma. Stabilization of the protein by mutation or interaction with other proteins prolongs its half-life, rendering it detectable by immunohistochemistry. Osteosarcoma is the most common primary canine bone tumor and is characterized by frequent early metastases. Multilobular tumors of bone involve primarily flat bones of the head and are low-grade ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 32 publications
7
55
0
Order By: Relevance
“…Immunoreactivity of the canine p53 protein towards CM-1 rabbit anti-human p53 polyclonal antibody (Sagartz et al, 1996;Gamblin et al, 1997;Wolf et al, 1997) and to the monoclonal PAb240 antibody (Teifke and Lohr, 1996) has been shown in immunohistochemical analyses of canine neoplasms. In order to further de®ne the immunoreactivity of canine p53, we used a panel of monoclonal antibodies in an immunoprecipitation assay (Figure 3b).…”
Section: Expression Of the Canine P53 Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoreactivity of the canine p53 protein towards CM-1 rabbit anti-human p53 polyclonal antibody (Sagartz et al, 1996;Gamblin et al, 1997;Wolf et al, 1997) and to the monoclonal PAb240 antibody (Teifke and Lohr, 1996) has been shown in immunohistochemical analyses of canine neoplasms. In order to further de®ne the immunoreactivity of canine p53, we used a panel of monoclonal antibodies in an immunoprecipitation assay (Figure 3b).…”
Section: Expression Of the Canine P53 Proteinmentioning
confidence: 99%
“…Recently similar mutations within the canine p53 gene have been identi®ed in a small number of canine cancer types including: thyroid carcinoma (Devilee et al, 1994), oral papilloma (Mayr et al, 1994), mammary tumours (Van Leeuwen et al, 1996), osteosarcoma (Van Leeuwen et al, 1997), circumanal gland adenoma (Mayr et al, 1997) and lymphoma (Veldhoen et al, 1998). Overexpression of the canine p53 protein was also observed in tumours of epithelial, mesenchymal and round cell origins (Sagartz et al, 1996;Gamblin et al, 1997;Wolf et al, 1997). The vast clinical knowledge concerning the identi®cation and treatment of canine cancers and the apparent similarity of p53 inactivation in the tumours of some cancer patients identi®es canine p53 as a potential target for anti-cancer therapy in the dog.…”
Section: Introductionmentioning
confidence: 98%
“…The p53 gene is reportedly mutated in the majority of human and canine cancers. [16][17][18][19][20][21][22][23][24][25][26] Mutations of the p53 gene are associated with a number of canine lymphoid and nonlymphoid cancers such as osteosarcoma, LSA, and various carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the mutant p53 protein has also been observed in canine tumors of epithelial, mesenchymal and round cell origins (Sagartz et al, 1996, Wolf et al, 1997. The expression of p53 assessed by real-time polymerase chain reaction (PCR), however, may be heterogeneous in mammary tumors such as adenoma, adenosarcoma and their metastasis in lymphnodes (Klopfleisch and Gruber, 2009).…”
mentioning
confidence: 99%